PENGARUH PEMANFAATAN MEDIA KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MENULIS KALIMAT SISWA TUNARUNGU - Mei Setiorini,; Abdul Huda; Saichudin Saichudin (Department of Special Education, 2014)
The research problem is how the results of learning to write sentences before and after the use of the word picture card media, as well as whether there are differences in learning outcomes before and after the use of the word picture card media. The purpose of this study was to determine the learning outcomes of students write sentences before and after the use of the word picture card media, as well as to determine whether there is difference in learning outcomes before and after picture of media use word cards to students' ability to write a sentence. This research used an experimental method